Casein composition and differential translational efficiency of casein transcripts in donkey's milk. Issue 2 (30th April 2019) - Cosenza, Gianfranco; Mauriello, Rosalba; Garro, Giuseppina; Auzino, Barbara; Iannaccone, Marco; Costanzo, Angela; Chianese, Lina; Pauciullo, Alfredo
Abstract: The amount of the four caseins (αs1, αs2, β and κ-CN) in donkey milk was evaluated by Urea-PAGE analysis at pH 8.6, followed by immuno-detection with polyclonal antibodies, coupled to densitometric analysis. The results showed the percentage of each casein in decreasing order: β (54.28) > αs1 (35.59) > αs2 (7.19) > κ-CN (2.79). The mRNA quantification of donkey casein transcripts, carried out by RT-qPCR, showed that the average percentage of corresponding gene transcripts ( CSN2, CSN1S1, CSN1S2 I and CSN3 ) was 70.85, 6.28, 14.23 and 8.65, respectively. The observed translation efficiency, assessed as percentage of single milk casein fraction out of single percentage of transcript, was 0.76, 5.66, 0.50 and 0.32, respectively. The analysis of the sequences flanking the start codon, the codon usage frequencies and the coding sequence length might explain, at least in part, the differential transcriptional and translational rate observed among the casein transcripts.